2007
DOI: 10.2298/aoo0702019v
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced non-small cell lung cancer, pretreatment prognostic factors: Disease stage, tumor histopathological characteristics, the patient-related factors

Abstract: Background: The existing tumor-node-metastasis staging system ignores numerous clinical, therapeutic, and biological characteristics of lung cancer and psychomotor condition of a patient because it is based on the anatomic extent of disease. Therefore, there is a possibility of inadequate choice of therapy for any individual patient. Based on the disease stage, histopathological characteristics of the tumor and the patient-related factors (sex, age, Karnofsky status, accompanying diseases) the outcome of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The addition of 3 unreported estimates supplied by article authors increased the size of our meta-analysis to 23 studies with 25 estimates. 29,30,49 Characteristics and demographic information as well as adjustment or restriction variables for included articles are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 3 unreported estimates supplied by article authors increased the size of our meta-analysis to 23 studies with 25 estimates. 29,30,49 Characteristics and demographic information as well as adjustment or restriction variables for included articles are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, previous studies have indicated that among patients with non-small cell lung cancer (NSCLC), survival was unaffected (6)(7)(8) or decreased by DM (9,10), and an elevated fasting blood glucose (FBG) level appeared to significantly increase the overall risk of mortality (11). However, the sample size of these studies was small or not appropriately indicated (9)(10)(11). Therefore, in the current study, strictly defined diagnostic guidelines for DM were utilized to investigate the prognosis of patients with lung cancer with coexisting DM in a large study cohort.…”
Section: Introductionmentioning
confidence: 83%
“…16,17 While some evidence has suggested that diabetes is associated with increased survival in lung cancer, several studies have shown the opposite. [18][19][20][21][22] A retrospective study evaluated the prognostic value of several clinical characteristics of 442 patients with advanced NSCLC receiving first-line, platinum-based doublet chemotherapy and concluded that the presence of diabetes at baseline was a significant negative prognostic factor for both progression-free survival (PFS) and overall survival (OS). 23 On the basis of these and other previously published data, improved treatment options for patients with diabetes and advanced NSCLC may be needed.…”
Section: Introductionmentioning
confidence: 99%
“…23 On the basis of these and other previously published data, improved treatment options for patients with diabetes and advanced NSCLC may be needed. [18][19][20][21]23 nab-paclitaxel in combination with carboplatin (nab-P/C) is approved for the first-line treatment of locally advanced or metastatic NSCLC in patients who are not candidates for curative surgery or radiation therapy. 9 In a large, multicenter phase 3 trial, firstline nab-P/C significantly improved the primary end point (overall response rate [ORR]) over solvent-based paclitaxel plus carboplatin (sb-P/C; 33% vs. 25%; response rate ratio [RRR], 1.313; 95% confidence interval [CI], 1.082-1.593; P ¼ .005), with a trend toward improved OS and PFS.…”
Section: Introductionmentioning
confidence: 99%